National conservation science conferences as a means of bridging conservation science and practice. Issue 5 (18th July 2018) - Roll, Uri; Iwamura, Takuya; Berger‐Tal, Oded
Abstract : Article impact statement : National conservation conferences provide benefits not currently served by meetings at other levels.